1971
DOI: 10.1104/pp.48.1.103
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic Acid Raises the Permeability of Plant Cells to Water

Abstract: A number of recent observations have indicated a role for abscisic acid in maintaining water balance. Treatment with ABA reduces the transpiration rate (3,5), probably by bringing about stomatal closure (2, 4). Furthermore, water stress leads to a significant increase in ABA concentration in leaves (5, 7). On the other hand, ABA increases the rate of root exudation (6).The present communication reports a marked effect of ABA on the permeability of plant tissues to water. The effect is observable both on Lp, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
0

Year Published

1972
1972
2002
2002

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(43 citation statements)
references
References 6 publications
3
40
0
Order By: Relevance
“…and wilting has obvious economic potential, as already mentioned by Jones and Mansfield (1970). Although many compounds that reduce transpiration are already known, the finding that ABA increases root exudation (Tal and Imber 1971), chloride accumulation (Mizrahi and Richmond, unpublished data), and the permeability of plant tissues to water (Glinka and Reinhold 1971) suggests a more complex mode of action than merely that of an antitranspirant. In addition, commercial utilization of ABA to improve water balance of water-stressed plants seems advantageous in that ABA is an endogenous material with a high turnover (Milborrow 1969;Milborrow and Nodle 1970), thereby diminishing problems of residual toxicity and deleterious metabolic side effects.…”
Section: ·2 0·4 2·04·0mentioning
confidence: 91%
See 1 more Smart Citation
“…and wilting has obvious economic potential, as already mentioned by Jones and Mansfield (1970). Although many compounds that reduce transpiration are already known, the finding that ABA increases root exudation (Tal and Imber 1971), chloride accumulation (Mizrahi and Richmond, unpublished data), and the permeability of plant tissues to water (Glinka and Reinhold 1971) suggests a more complex mode of action than merely that of an antitranspirant. In addition, commercial utilization of ABA to improve water balance of water-stressed plants seems advantageous in that ABA is an endogenous material with a high turnover (Milborrow 1969;Milborrow and Nodle 1970), thereby diminishing problems of residual toxicity and deleterious metabolic side effects.…”
Section: ·2 0·4 2·04·0mentioning
confidence: 91%
“…Cytokinins increase transpiration by effecting stomatal opening (Livne and Vaadia 1965;Meidner 1967;Luke and Freeman 1968), and abscisic acid (ABA) effects closure of stomata and consequent reduction of transpiration (Little and Eidt 1968;Mittelheuser and Van Steveninck 1969;Jones and Mansfield 1970;Mizrahi, Blumenfeld, and Richmond 1970), as well as enhancement of root exudation (Tal and Imber 1971). It was also reported recently that ABA increases the permeability of plant tissues to water (Glinka and Reinhold 1971). In addition, work on a wilty tomato mutant has shown that the impairment of the closure of its stomata may be corrected by treatment with ABA (Imber and Tal 1970).…”
Section: Introductionmentioning
confidence: 98%
“…Exogenously applied as well as endogenously produced ABA hardened plants to exposure to low temperatures (18,19). ABA is known to cause stomatal closure (16,20) and has been reported to alter root permeability to water (5,(7)(8)(9)13). In experiments where ABA is added to the irrigation water (18), it is often unclear whether the hormone acts on the root or is transported to the shoot and directly effects the stomata.…”
Section: Introductionmentioning
confidence: 99%
“…Water uptake during the imbibition period (up to about 8 h after sowing) is not influenced by ABA. It thus seems unlikely that ABA acts in germination by impairing the water permeability of membranes (8). It rather appears appropriate to discuss the action of ABA in terms of the water potential equation (Iw = IP + I, + I').…”
mentioning
confidence: 99%